Food value chains: Increasing productivity, sustainability, and resilience to climate change - de Brauw, Alan; Pacillo, Grazia (International Food Policy Research Institute, 2022)
Climate change will drive responses and adaptations throughout agrifood systems. Changes in growing conditions for many crops will alter agricultural production patterns. Along with these shifts in crop production, rising temperatures, changes in humidity levels, and increased extreme weather will also affect the value chains through which agricultural products are traded, aggregated, processed, and sold to consumers. This chapter illustrates how incentives for producers and other value chain actors will change as climate change reduces the effectiveness of inputs, such as herbicides and pesticides, increases the risks of spoilage faced by middlemen and retailers, and potentially leads to increases in transaction costs. Whole value chains may be affected from farmer to consumer; for example, if international shipping costs rise with increasing fuel costs, export-oriented chains for select products in some countries may become unprofitable and even disappear. Although research has largely neglected the impacts of climate change on value chains beyond the farm, one thing is clear — many value chain actors along with farmers will need to adapt to new realities, as they showed they were capable of in the face of disruptions from the COVID-19 pandemic.